IRAN REVOLUTION, ECONOMIC STRUGGLE AND INDEPENDENCE UNDER THE PRESSURE - Meirison Alizar Sali (Hunafa: Jurnal Studia Islamika, 2019)
Abstract. Iran is a country that has great potential to achieve progress because it has a strong and independent recruitment system. However, the American Embargo has stifled the Iranian economy, but with certain steps and weapons of oil and gas that can be used as weapons, changes to laws that support investments that have received protests from conservatives continue. Will Iran succeed in realizing independence in the Industrial field? The author conducts discussions with qualitative methods and conducts literature studies to collect data and get it directly from official sources from the Iranian embassy in Jakarta. After experiencing various kinds of changes in economic policy and facing various kinds of situations Iran succeeded in developing the economy without changing the basics of Islamic shari'ah principles and revolution. Keywords: Iranian Revolution, Economic Struggle and Independence, Pressure